Annealing Influence on Nanostructure’s Optical Properties CdS Thin Films Prepared by Physical Vapor Deposition Technique - Abbas, Esraa A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this work, the influence of the annealing temperature on the optical properties of the thin films Cadmium Sulphide (CdS) has been studied. Thin films of Cadmium Sulphide (CdS) were made using the Physical Vapor Deposition (PVD) method. The optical properties of annealing temperatures (as deposited, 200, 250, and 300 ) were scrupulous. The UV/VIS spectrophotometer investigated optical parameters such as transmission, the coefficient of absorption and energy gap of the films for the range (400-110 nm) as an assignment of the annealing temperature. The optical properties were calculated as a function of annealed temperature: absorption, transmission, reflection, band gap, coefficient of absorption, excitation coefficient and index of refraction.